Pengaruh Citra Merek, Customer Review, Dan Kepercayaan Terhadap Keputusan Pembelian Online Pada Marketplace Shopee (Studi Kasus pada Mahasiswa FEB Universitas Islam Malang) - Cahyaningrum, Dwi Annisa; Hidayati, Nur; Mustapita, Arini Fitria (E-JRM : Elektronik Jurnal Riset Manajemen, 2024)
Abstract This study aims to determine and analyze the effect of brand image, customer reviews and trust on online purchasing decisions at the Shopee marketplace, a case study of FEB students at the Islamic University of Malang. The number of samples in the study were 80 respondents. The analysis method used in this research is multiple linear regression analysis using the SPSS application. The results of this study indicate that brand image and customer reviews partially affect online purchasing decisions on the Shopee marketplace, while trust partially has no effect on online purchasing decisions on the Shopee marketplace. Keywords: Brand Image, Customer Review, Trust, Purchasing Decisions